2011
DOI: 10.1002/jor.21335
|View full text |Cite
|
Sign up to set email alerts
|

Anterior border of the tibia as a landmark for extramedullary alignment guide in total knee arthroplasty for varus knees

Abstract: A disadvantage to using extramedullary alignment guides of the tibia for total knee arthroplasty (TKA) is difficulty in correctly identifying the ankle center. The anterior border of the tibia is easily palpable, as it is not covered by muscles and its shape is convex anteriorly. We hypothesized that appropriate points exist along the anterior border that can be used as landmarks for extramedullary guides. Prior to TKA, computed tomographic images of the entire tibia were obtained from 101 osteoarthritic knees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…For two knees, we were able to perform a computer simulation based on preoperative CT data to evaluate the relationship between a line connecting the proximal and distal one-third of the anterior border and the mechanical axis of the tibia. The discrepancy of one knee relative to the target angle was 0.4°varus, while that of the other knee was 0.4°valgus, results that were similar to those of our previous computer simulation study [21]. …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…For two knees, we were able to perform a computer simulation based on preoperative CT data to evaluate the relationship between a line connecting the proximal and distal one-third of the anterior border and the mechanical axis of the tibia. The discrepancy of one knee relative to the target angle was 0.4°varus, while that of the other knee was 0.4°valgus, results that were similar to those of our previous computer simulation study [21]. …”
Section: Resultssupporting
confidence: 90%
“…Tibial components with a varus alignment over 3°have a higher incidence of failure because of the increased stress on cancellous bone [8,29] and increased proximal tibial strain, above the threshold for fatigue damage [30]. We previously performed a three-dimensional computer simulation to identify a reliable reference point for setting the guide [21]. In that study, we found that a line connecting the proximal and distal one-third of the anterior border was similarly parallel to the mechanical axis in the coronal plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid determining the ankle center, some surgeons have used the anterior border of the tibial shaft for the extramedullary guide. Recently, it has been reported that a line connecting the medial one-third of the patellar tendon attachment and the distal one-fourth of the anterior border of the tibia is highly consistent and parallel to the mechanical axis in the frontal plane [9]. However, the anterior border of the tibia is not always easily palpable in patients with high levels of dermal fat.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors emphasise the usefulness of bony landmarks of extramedullary reference for tibial cutting. Fukagawa et al [21] suggested that the medial one third of the patellar tendon attachment and the distal one fourth of the anterior border of the tibia was consistently parallel to the mechanical axis in the coronal plane. Tsukeoka et al [22] mentioned that the anterior tibial crest in the coronal and sagittal planes could be a useful EM guideline in performing TKAs.…”
Section: Discussionmentioning
confidence: 99%